Strategi Guru dalam Menginternalisasi Nilai Pancasila di Madrasah Ibtidaiyah: Studi Kasus Pembelajaran PKn di MI Pekanbaru - Zulhidah; Nabiha; Fatimah Azzahra; Nurul Hasanah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Abstract The moral decline among Indonesian students necessitates early character education, particularly within Madrasah Ibtidaiyah (MI), which offers a strategic Islamic educational ecosystem. This study aims to analyze the strategies, challenges, and innovative solutions employed by Civic Education teachers in internalizing Pancasila values at the elementary madrasah level. Employing a qualitative descriptive approach with a single-case study design, data were collected through semi-structured interviews and classroom observations at an MI A in Pekanbaru, and analyzed using the Miles and Huberman model (data reduction, display, and verification). The findings reveal that Pancasila values were effectively internalized through contextual methods (roleplay, rhythmic songs, and real-life examples) and digital video media, which proved superior to physical posters. The integration of the First Principle with Islamic routines (Tahfidz and Dhuha prayer) naturally fostered a religio-nationalist character. Key challenges included limited reading literacy among lower-grade students and psychosocial-domestic influences, which were mitigated through teachers’ affective sensitivity, WhatsApp-based parent collaboration, and personalized interventions. Consequently, this study recommends the implementation of the